Ecological risk assessment of cities on the Tibetan Plateau based on land use/land cover changes – Case study of Delingha City. (June 2019) - Jin, Xin; Jin, Yanxiang; Mao, Xufeng
Highlights: From 1986 to 2015 the land use/land cover changes in the south of the Delingha City were more concentrated and significant. High ecological risk areas are mainly located in the low-lying and flat landscapes in the south. During the research period, the overall ecological environment in Delingha City improves. Abstract: Land use/land cover and its change is a certain reflection of the interaction of natural factors and human activity in regional ecological environment, and the change of land use/land cover also affects the regional ecological process. Among regional ecological assessments, the landscape ecological risk assessment by land use/land cover changes is a regional ecological risk assessment method that is based on spatial pattern perspectives. The research on typical ecological fragile areas that respond strongly to global change focuses on coastal zones, wetlands and transition zones between cropping areas and nomadic areas; however, there are no related studies on the Tibetan Plateau. This study proposed an ecological risk assessment on Delingha City on the Tibetan plateau by using RS (remote sensing) and GIS (geographic information system) methods Based on land use/land cover variations in Delingha City during the periods 1986–2000 and 2000–2015, regional ecological risk changes were analysed to provide scientific bases for the ecological protection of cities on the Tibetan Plateau. The results indicated that: 1) From 1986 to 2000, major land use/land cover changes took place in the south of the city; in general, grassland was converted into farmland. From 2000 to 2015, the spatial distribution of land use changes was chaotic; however, the land use changes in the south were more concentrated and significant. 2) More than half of Delingha City fall under low ecological risk zones, which are mainly located in high-altitude mountainous area in north Delingha. High ecological risk areas are mainly located in the low-lying and flat landscapes in the south. 3) During the research period, the significant decrease of highest- and high-risk zones and considerable increase of low-risk zone indicate an improvement of the overall ecological environment in Delingha City through 1986–2015.